2015
DOI: 10.1002/joc.4591
|View full text |Cite
|
Sign up to set email alerts
|

Impacts of and adaptation to inter-decadal marine climate change in coastal China seas

Abstract: ABSTRACT:The coastal China areas stretching from tropical to temperate zone represent major environmental and economic assets. However, knowledge of climate change and its impact in coastal seas, which is very critical for marine resource and risk-management issues, is relatively poor compared with that on land. Here, we show that the coastal China seas experienced a long-term surface warming with a rate of 0.015 ∘ C year −1 and an obvious sea level rise along the coast, particularly along the East China Sea w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

4
35
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
7
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 52 publications
(39 citation statements)
references
References 17 publications
4
35
0
Order By: Relevance
“…At present, extreme water temperature events can cause shifts in species ranges, local extinctions, and economic loss on aquaculture and seafood industries [9][10][11]. For instance, the rapid warming of the ECSs has been linked to frequent occurrences of harmful algae blooms and northward shifts of marine fishes [12]. A Chinese Marine Disaster Bulletin from 2012 [13] indicated that severely harmful algae occurred at the coast of the southern ECS, causing a direct economic loss of two billion RMB.…”
Section: Introductionmentioning
confidence: 99%
“…At present, extreme water temperature events can cause shifts in species ranges, local extinctions, and economic loss on aquaculture and seafood industries [9][10][11]. For instance, the rapid warming of the ECSs has been linked to frequent occurrences of harmful algae blooms and northward shifts of marine fishes [12]. A Chinese Marine Disaster Bulletin from 2012 [13] indicated that severely harmful algae occurred at the coast of the southern ECS, causing a direct economic loss of two billion RMB.…”
Section: Introductionmentioning
confidence: 99%
“…There is a regionality to the ocean surface warming rate due to discrepancies in atmospheric circulation and ocean currents and the heterogeneous distribution of aerosols [22][23][24] . Previous studies have investigated the regional climate, marine environment and ecosystem in the offshore areas of China and adjacent seas (hereafter, offshore China) during the two periods of global warming [25][26][27][28][29][30] because this region is an important component of coastal boundary systems, which provide 10.6% of primary production and 28.0% of global fishery production 24 . Since the late 1970s, the SST in offshore China (including the East China Sea (ECS) and South China Sea (SCS)) has rapidly increased [25][26][27]29,30 , and the warming rate has been approximately five times as fast as the global mean SST warming rate during the warming acceleration period 28 .…”
mentioning
confidence: 99%
“…First, soft options exist, such as local planning for storm preparedness and recovery (Anthony et al, 2015). Forecasting and response capabilities to coastal disasters can be improved with prevention and management systems (Cai et al, 2015). Hard solutions, like coastal infrastructure for flood protection, can compensate the loss of natural coastal protection (Cai et al, 2015).…”
Section: Adapt To the Loss Of Coastal Protectionmentioning
confidence: 99%
“…Forecasting and response capabilities to coastal disasters can be improved with prevention and management systems (Cai et al, 2015). Hard solutions, like coastal infrastructure for flood protection, can compensate the loss of natural coastal protection (Cai et al, 2015). In case of situations where conditions do not allow for coastline protection, compensatory measures can be taken such as investments in social protection and alternative livelihoods (Anthony et al, 2015).…”
Section: Adapt To the Loss Of Coastal Protectionmentioning
confidence: 99%